Quantification of biological contamination by exotic tree species in an araucaria forest fragment in lages, Santa Catarina state Quantificação da contaminação biológica por espécies arbóreas exóticas em um fragmento de floresta ombrófila mista em lages - SC - Spiazzi F.R.* (2017)
© 2017 Ciência Florestal, Santa Maria, All right reserved.The present study aimed to evaluate the biological contamination over time in a tree community of Montane Araucaria forest, in advanced successional stage, adjacent to a Pinus taeda L. plantation, in Lages, SC state. For this sake, a total of, 20 x 20m, 25 plots, distributed in five transects with five plots each, were allocated perpendicular to the edge in contact with the pinus plantation. In each plot, all living trees were measured (cbh ≥ 5 cm, measured at 1.30 m above soil level), collected and identified. Four years after the first inventory, the same individuals were re-inventoried, the dead individuals and survivor quantified and recruits added. For the two evaluated years, phytosociological descriptors were calculated, indicators of biological invasion quantified for all community as well as for ecological groups and the demographic rates determined. A total of 73 and 74 species were sampled in the first and second years, among of them two exotic species: Pinus taeda and Ligustrum lucidum W.T. Aiton. Both species showed low values of the invasion indicators, but with an increment in the participation of Pinus taeda among pioneer species over time. Results of demographic rates suggest that, for different ecological groups, the invasion process is in distinct stages. We conclude that the pioneer species was the most affected component by biological invasion, which reinforces the need for analysis considering the different ecological groups.